2007
DOI: 10.1007/s11606-007-0390-2
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Quality of Primary Care and Hospitalization for Coronary Heart Disease in England: National Cross-sectional Study

Abstract: The lack of an association between quality scores and admission rates suggests that improving the quality of primary care may not reduce demands on the hospital sector and that other factors are much better predictors of hospitalization for coronary heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 12 publications
2
49
1
1
Order By: Relevance
“…In studies of the UK Quality and Outcomes Framework, in which incentives were directly tied to measured quality of care, any observed decreases in hospital admissions accompanying observed changes in quality were small, [25][26][27] and some studies found no association between measured quality and hospital admissions. 28,29 Research to date, largely from the United Kingdom and United States, has provided mixed evidence of the effectiveness of these programs. 24,[30][31][32][33][34] Studies of Ontario's pay-forperformance initiatives showed modest improvements in delivery of some preventive services 35,36 and no change in management of patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies of the UK Quality and Outcomes Framework, in which incentives were directly tied to measured quality of care, any observed decreases in hospital admissions accompanying observed changes in quality were small, [25][26][27] and some studies found no association between measured quality and hospital admissions. 28,29 Research to date, largely from the United Kingdom and United States, has provided mixed evidence of the effectiveness of these programs. 24,[30][31][32][33][34] Studies of Ontario's pay-forperformance initiatives showed modest improvements in delivery of some preventive services 35,36 and no change in management of patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…39 Most research in this area focuses on care for individual diseases, using the delivery of specific services as indicators of quality. 24,[30][31][32][33][34] Evidence of the effect of incentive-based programs on broader outcomes such as access to primary care, continuity of care, 40 hospital admissions [25][26][27][28][29]41,42 and overall resource use 30,34,43 has been inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Although the QOF was intended to improve care for long‐term conditions and to reduce hospital admissions, there is only a weak negative correlation between ACSCs and QOF points. This may be because there are both negative and positive correlations between admissions for particular ACSCs and the QOF clinical indicators for management of those conditions (Downing et al ., 2007; Bottle et al ., 2008; Dusheiko et al ., 2011; Purdy et al ., 2011). The three patient‐reported measures are reasonably highly correlated with each other but much less well correlated with the QOF measures.…”
Section: Alternative Measuresmentioning
confidence: 99%
“…The literature suggests that incentive payments have led to mixed results across various jurisdictions, [3][4][5][6] including the Quality and Outcomes Framework in England, [7][8][9][10][11] and in Canada. 12,13 Furthermore, the term pay for performance can have a range of meanings.…”
Section: Evaluation Of Incentive Payments and The Incentive Programmentioning
confidence: 99%